Seizures and epilepsy in cats - Moore SA (Dove Medical Press, 2014)
Sarah A Moore Department of Veterinary Clinical Sciences, The Ohio State University, Columbus, OH, USA Abstract: Seizures are a common presenting complaint in cats, although causes and options for the treatment of seizures in this species have been historically poorly described in the veterinary literature. Seizure manifestation in cats may be different than what is typically seen in dogs, but the underlying causes of seizure activity are the same. These include primary epilepsies, structural epilepsies, and reactive seizures. Although primary epilepsy was once believed to be rare in cats, we now commonly appreciate this syndrome, albeit at a lower frequency than in dogs. Because of this, a complete diagnostic work-up is recommended for all cats presenting for initial evaluation of seizures. Symptomatic treatment of seizures in cats is similar to dogs, with only a few limitations related to species-specific antiepileptic drug toxicities. The goal of this review is to summarize the recent veterinary literature related to feline seizures, with a focus on seizure classification, clinical manifestation, diagnostic evaluation, and treatment options. Keywords: antiepileptic drug, seizure classification, levetiracetam, zonisamide, phenobarbital